Three-dimensional Morphing and Its Added Value in the Rhinoplasty Consult - Lekakis, Garyfalia (Plast Reconstr Surg Glob Open, 2019)
BACKGROUND: The evolving literature on 3D surface imaging demonstrates that this technology is becoming the preferred simulation technique in hospitals and research centers. However, no study has demonstrated before the superiority of this facility over standard 2D simulation during preoperative evaluation in rhinoplasty. METHODS: One hundred seventy-two consecutive patients requesting rhinoplasty were included. Patients answered a questionnaire following a 2D simulation and subsequently experienced 3D morphing. A single question was answered regarding the added value of the latter by patients and surgeons, respectively. RESULTS: In our survey, satisfaction with 2D morphing reached 61%. Ninety-five percentage of the same group considered 3D simulation an added value over 2D. Additionally, 84% of patients requesting revision rhinoplasty admitted that 3D computer simulation has helped them understand the aims of surgery, in contrast to 61% of patients from the primary group. Furthermore, patients unsatisfied with their 2D simulation got reassured following 3D simulation to undergo surgery at a higher percentage (67%), compared with the group initially satisfied with 2D (48%). Women appeared reassured by 3D imaging in higher percentage (63%) compared with men (42%). The 2 surgeons, however, found 3D simulations to be an added value in 66% and 74% of all patients. CONCLUSIONS: The overwhelming majority of our patients considered 3D simulation an added value over 2D. Patients initially unsatisfied with 2D morphing, revision rhinoplasty patients, and women seemed to be the groups that appreciated more 3D than 2D computer simulation. In contrast, surgeons considered the facility of 3D an added value in two-thirds of the patients.